Metal-ion oligomerization inside electrified carbon micropores and its effect on capacitive charge storage - Wei, Jiaqi (2022)
Ion adsorption inside electrified carbon micropores is pivotal for the operation of supercapacitors. Depending on the electrolyte, two main mechanisms have been identified so far, the desolvation of ions in solvents and the formation of superionic states in ionic liquids. Here, it is shown that upon confinement inside negatively charged micropores, transition-metal cations dissolved in water associate to form oligomer species. They are identified using in situ X-ray absorption spectroscopy. The cations associate one with each other via hydroxo bridging, forming ionic oligomers under the synergic effect of spatial confinement and Coulombic screening. The oligomers display sluggish dissociation kinetics and accumulate upon cycling, which leads to supercapacitor capacitance fading. They may be dissolved by applying a positive potential, so an intermittent reverse cycling strategy is proposed to periodically evacuate micropores and revivify the capacitance. These results reveal new insights into ion adsorption and structural evolution with their effects on the electrochemical performance, providing guidelines for designing advanced supercapacitors.